Radially selective inward transport of positrons in a Penning–Malmberg trap - A Deller; T Mortensen; C A Isaac; D P van der Werf; M Charlton (New Journal of Physics, 2014)
The anharmonic component of the electric field of a Penning–Malmberg trap is exploited to manipulate a subset of the radial ( r ) distribution of trapped positrons, using a dipole field made to rotate about the long-axis ( z ) of the trap. This ‘rotating wall’ technique (RW) induces inward transport at frequencies associated with the motion of trapped particles, although similarly it causes heating. The motional frequencies vary spatially within a non-ideal trap, thus resonant interaction with the rotating field may be restricted to a region selected to lie away from the trap centre, thereby forming a pseudo-potential barrier and reducing losses due to both heating and expansion. We demonstrate this effect for improved accumulation of positrons and further outline a technique to achieve strong compression with low RW amplitudes by chirping the drive frequency.